"Girls should cook, rather than kick!" – Female soccer players under stereotype threat. (September 2016) - Hermann, Johanna M.; Vollmeyer, Regina
Abstract: Based on the stereotype threat theory (Steele & Aronson, 1995), we tested if female soccer players' performance decreased when the stereotype, " females are bad at soccer, " was activated. Additionally, girls under stereotype threat were assumed to experience lower flow while playing soccer and to be more worried, as compared to those in the control condition. The hypotheses were tested in three German soccer clubs ( N  = 36; age: M  = 14.94, SD  = 1.22). Participants completed a dribbling task two times (pre-post design) while their time was recorded. Flow and worry were assessed after each dribbling task. In between the two dribbling tasks, the girls read an article about either the incompetence of female soccer players or the growing popularity of soccer. The results showed that girls in the stereotype threat condition needed significantly more time to complete the dribbling task than did those in the control condition. No differences between the two conditions were observed with regard to flow and worry. These findings are discussed in terms of different mediating processes postulated in the stereotype threat literature focusing on sports. Highlights: Stereotype threat effect in young female soccer players. Flow (automated routines) was not influenced by stereotype threat. Worry did not mediate the stereotype threat effect. Stronger worry increased the dribbling performance.